Exposure to renin-angiotensin system inhibitors before kidney transplantation is associated with a decreased risk of delayed graft function - Liang, Gan Zhen; Dorais, Marc; Collette, Suzon; Sénécal, Lynne; Belkaid, Majda; Turgeon, Julie; Cardinal, Héloïse (Frontiers in Immunology, 2024)
IntroductionAnimal models suggest a protective role of angiotensin-converting enzyme inhibitors (ACEi) and angiotensin-II receptor blockers (ARBs) in reducing renal and cardiac ischemia-reperfusion injury. Our aim was to determine the association between pre-transplant ACEi/ARBs use and the occurrence of delayed graft function (DGF) in patients who received a kidney transplantation from a deceased donor.MethodsConsecutive recipients between 2008 and 2021 in 2 Canadian university-affiliated centers were included in this retrospective cohort study. The main outcome was the occurrence of DGF and the exposure was use of ACEi or ARBs at the time of admission for transplantation. Mixed models were fit.ResultsA total of 897 patients were included, of which 160 (18%) experienced DGF. At admission, 337 (38%) patients were exposed to ACEi/ARBs. In the multivariable analysis, pre-transplant ACEi/ARBs use was associated with a reduced risk of DGF (odds ratio: 0.60, 95% confidence interval: 0.40, 0.92). Other factors associated with DGF were recipient obesity, donor type, ethnicity, age, hypertension, and total ischemia time.DiscussionPre-transplant use of ACEi/ARBs is associated with a lower risk of DGF in early postoperative period, which may be due to a protective effect of these agents on renal ischemia-reperfusion injury.